Patterns of Ear Disease in Upazila Health Complex Outpatient Department, Boalkhali, Chattogram (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Ear diseases are a significant public health concern in Bangladesh, affecting individuals of all ages and socioeconomic backgrounds. The burden of ear diseases significantly impacts the quality of life of affected individuals, leading to hearing impairment, communication difficulties, and reduced social and economic opportunities. To assess the pattern of ear diseases among the patients attending Outpatient Department (OPD) of Boalkhali Upazila Health Complex, Chattogram.  Materials and methods: A cross-sectional type of  observational study was carried out at ENT Outpatient Department (OPD) of Boalkhali Upazila Health Complex, Chattogram in between June 2015 to January 2019. In this study 2142 patients were identified with ear diseases after screening of 5100 patients attending at ENT OPD.Results: 42.8% patients were diagnosed after screening the 5100 patients at ENT OPD where male female ratio was 1:1.2. Most of the patients (32.6%) were from the age group in between 0-18 years of age and a minimum of 9.2% patients were above 60 years old. Mostly identified diseases were CSOM (11.7%), otalgia (9.7%), AOM (7.3%), ASOM (6.8%), impacted wax (5.5%) and tinnitus (5.5%). But only a few of 0.6% were diagnosed as squamous cell carcinoma. Among the 15 common clinical conditions in this study, it was found that female patients were predominant in all cases except in impacted was, foreign body in ear and furunculosis.  Conclusion: This study highlights the need for further research and action to address the burden of ear diseases in Bangladesh and improve the ear care outcomes for its population.JCMCTA 2023 ; 34 (2) : 31-35